Progress in plasma wakefield acceleration driven by a short intense bunch of relativistic electrons - Onishchenko, I.N. (Вопросы атомной науки и техники, 2006)
The recent experimental results on frontier values of accelerating gradient and energy gain achieved by advanced acceleration methods based on intense plasma wakefields driven by a high-power short laser pulse or a large charge electron bunch are overviewed. Physical principles are considered for high-gradient acceleration of charged particles with purpose to elaborate the concept of future compact accelerators, which are called for high-energy physics and high technology applications, and also for creation of contemporary short pulsed radiation sources. The results of investigations on laser plasma wakefield accelerator (LWFA) generating precise monoenergtic beams with a small angle divergence and on plasma wakefield accelerator (PWFA) achieving breakdown through GeV barrier energy gain at SLAC by use wakefield excited by a short intense electron bunch in 1 m length plasma are presented. The possibility of PWFA application to doubling the energy of a future linear collider without doubling its length is considered.